Macrophage phagocytic activity toward adhering staphylococci on cationic and patterned hydrogel coatings versus common biomaterials. (May 2015) - da Silva Domingues, Joana F.; Roest, Steven; Wang, Yi; van der Mei, Henny C.; Libera, Matthew; van Kooten, Theo G.; Busscher, Henk J.
Graphical abstract: Abstract: Biomaterial‐associated-infection causes failure of biomaterial implants. Many new biomaterials have been evaluated for their ability to inhibit bacterial colonization and stimulate tissue-cell-integration, but neglect the role of immune cells. This paper compares macrophage phagocytosis of adhering Staphylococcus aureus on cationic-coatings and patterned poly(ethylene)glycol-hydrogels versus common biomaterials and stainless steel in order to identify surface conditions that promote clearance of adhering bacteria. Staphylococci were allowed to adhere and grow on the materials in a parallel-plate-flow-chamber, after which murine macrophages were introduced. From the decrease in the number of adhering staphylococci, phagocytosis-rates were calculated, and total macrophage displacements during an experiment determined. Hydrophilic surfaces had the lowest phagocytosis-rates, while common biomaterials had intermediate phagocytosis-rates. Patterning of poly(ethylene)glycol-hydrogel coatings increased phagocytosis-rates to the level of common biomaterials, while on cationic-coatings phagocytosis-rates remained relatively low. Likely, phagocytosis-rates on cationic coatings are hampered relative to common biomaterials through strong electrostatic binding of negatively-charged macrophages and staphylococci. On polymeric biomaterials and glass, phagocytosis-rates increased with macrophage displacement, while both parameters increased with biomaterial surface hydrophobicity. Thus hydrophobicity is a necessary surface condition for effective phagocytosis. Concluding, next-generation biomaterials should account for surface effects on phagocytosis in order to enhance the ability of these materials to resist biomaterial-associated-infection.